The Relationship between Systemic Functional Linguistics and Translation - Mathura, S. (My University, 2018)
Language is a symbol by which a community communicates among itself. Human being is part and parcel of one’s social group or more. All activities in a society are carried out with the use of particular language. Without language human society is unrealistic. Language serves as a link between each other in a group to express one’s thoughts and feelings. Every community is identified by its activities through a language. Generally, a language is related to the vocal system adopted in a society. Primarily a language plays an important role in formulating an efficient legal system to build up a civilized society. In the same way Grammar is also equally important in building up the basic structure of a language. Language gives an expression for the activities that take place in a society. The application of a language depends on the various activities formed in a society. There by a language is better understood through direct experience. Since linguistic deals with the study of language and how this works, and since the process of translation vitally entails language, the relevance of linguistics to translation should never be in doubt. But it must immediately be made clear that we are referring in particular to those branches of linguistics which are concerned with the social aspect of language use, and which locate the source text and target text firmly within the cultural context. Fawcett suggests, the link between linguistics and translation can be two-fold. On one hand, the finding of linguistics can be applied to the practice of translation, on the other hand, it is possible to establish a linguistic theory of translation. In 1965, Catford opened his A Linguistic Theory of translation, with the following assertion: any theory of translation must draw upon a theory of language – a general linguistic theory. Literal, free and faithful translations are more systematic approaches to the study of translation emerged and they are linguistically oriented thereby Vinay Darbelnet, Mounin, and Nida also put forward the aspects of translation theories related to the systematic linguistic aspects.